Improving gut microbiome through diet rich in dietary fibre and polyphenols: The case for orange peels - Ayokunle Olubode Ademosun; Olufunke Florence Ajeigbe; Mary Tosin Ademosun; Omodesola Oluwafisayo Ogunruku; Ganiyu Oboh (Human Nutrition & Metabolism)
The search for cost-effective and innovative dietary fiber sources that promote probiotic growth and support healthy gut microbiota development has become increasingly important in food product innovation. The gut microbiota is crucial for various physiological functions, such as nutrient absorption, immune system enhancement, gut structural integrity, and detoxifying harmful substances. One effective way to foster a beneficial relationship with gut microbiota is through dietary choices, which significantly affect the microbiota's structure, composition, metabolism, and overall function. Notably, orange peels not only promote the growth of probiotic bacteria but also enable these beneficial microbes to convert the polyphenols in the peels into even more healthful forms. The combination of probiotics and orange peels can lead to the creation of synbiotics, which are functional foods aimed at improving human health. In contrast, the typical Western diet, high in refined sugars, trans fats, and sodium, negatively impacts gut health and the growth of beneficial gut microorganisms. To enhance gut microbiota health, there should be a focus on food products low in processed sugars, sodium, and unhealthy fats, while being high in dietary fiber and polyphenols. Orange peels are particularly notable for their high levels of dietary fiber and polyphenolic compounds, both of which can positively affect the growth of beneficial gut microorganisms.